Effect of filtrating medium resistance on cassava pulp dewatering - Kolawole, P.; Agbetoye, L.A.S.; Ogunlowo, A.S. (2012)
Cassava pulp dewatering by applying pressure on the grated pulp was carried out. Pulp particles were constrained while the liquid was free. The cassava pulp cake was compressed. Experimental equipment was designed to obtain the applied pressure from various devices and the final moisture content of resulting cake was compared. Hydraulic jack press reduced the moisture content of cake to the acceptable level for gari production at a pressure of 69000 N/m2 and to a moisture content of 40%- 45%wet basis, Pulp particles capable of creating resistances within the filtering medium were identified.